2003
DOI: 10.1046/j.1365-2745.2003.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Self/non‐self discrimination in roots

Abstract: Summary 1Competition usually involves the allocation of limiting resources to non-reproductive functions. Natural selection is expected to favour mechanisms that increase competition with non-self neighbours and limit wasteful competition with self. 2 We used Pisum sativum plants that had two roots and 'double plants' with two shoots and two roots that could be either longitudinally separated into two genetically identical but physiologically distinct individuals or left intact. 3 Root development was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
228
5
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(253 citation statements)
references
References 64 publications
5
228
5
11
Order By: Relevance
“…The varied shoot responses of these accessions in response to root and shoot constraint suggest that there could be direct signals to regulate shoot growth in addition to indirect consequences of root allocation under root constraint. Our analysis of plant height under shoot/root constraint (Figure 3) and recent reports showing that root and shoot competition interact (Gersani et al, 1998;Falik et al, 2003;Lankinen, 2008) support this possibility.…”
Section: Discussionsupporting
confidence: 81%
“…The varied shoot responses of these accessions in response to root and shoot constraint suggest that there could be direct signals to regulate shoot growth in addition to indirect consequences of root allocation under root constraint. Our analysis of plant height under shoot/root constraint (Figure 3) and recent reports showing that root and shoot competition interact (Gersani et al, 1998;Falik et al, 2003;Lankinen, 2008) support this possibility.…”
Section: Discussionsupporting
confidence: 81%
“…In the field experiment, tendrils were more likely to coil around unconnected neighbours than around neighbours connected via rhizomes. These data suggest that, similar to root self-discrimination [7][8][9], self-discrimination in C. japonica tendrils is mediated by physiological coordination between the tendril and the touched plant. On the other hand, genotype-specific discrimination, as in the case of self-incompatibility and in the immune response, may not play a major role in the self-discrimination in C. japonica tendrils.…”
Section: Discussionmentioning
confidence: 70%
“…Root discrimination allows plants to change their root allocation and morphology in response to either self or non-self neighbours [6][7][8][9][10][11][12]. Root discrimination is thought to be mediated by environmentally based physiological coordination rather than by genotype-specific differences as in self-incompatibility and immune systems [7][8][9] (however, see [10]). For example, Gruntman & Novoplansky [9] have demonstrated that clones derived from the same plant become related to each other as genetic aliens after temporal separation.…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions in which there is the presence of neighboring plants, the plants perceive it, and the root system is able to develop in order to allow a greater increment of root dry mass, occurring more in the direction of the neighboring plant than of its own roots (Bianchi et al, 2006). A process occurs in which the plant avoids its own roots, and this allows them to minimize waste in the allocation of carbohydrates, in order to overcome the competition against itself (Falik et al, 2003).…”
Section: Resultsmentioning
confidence: 99%